Cephalometric findings among children with velopharyngeal dysfunction following adenoidectomy—A retrospective study. (24th April 2017) - Kassem, F.; Ebner, Y.; Nageris, B.; Watted, N.; DeRowe, A.; Nachmani, A.
Abstract : Objectives: To characterise the craniofacial structure by cephalometry, especially the skull base and nasopharyngeal space, in children who underwent adenoidectomy and developed persistent velopharyngeal dysfunction (VPD). Design: Retrospective study. Setting: Speech and swallowing clinic of a single academic hospital. Participants: Thirty‐nine children with persistent VPD following adenoidectomy (mean age 8.0±3.6 years) and a control group of 80 healthy children. Main outcome measures: Cephalometric landmarks were chosen; craniofacial linear and angular dimensions were measured and analysed. Results: The linear dimensions of the nasopharyngeal area were shorter in the VPD group, S‐Ba (41.6±4.2 mm, P <.05) and S‐Ptm (42.4±5.1 mm, P <.05). The anterior skull base, N‐S, was similar (68.1 mm±6.8). The velum length, Ptm‐P was significantly shorter in the VPD group (27.8±4.3 mm, P <.001). The Ba‐S‐Ptm angle was significantly larger in the VPD group (63.5±5.6°, P <.001). There was no significant difference in cranial base angle (CBA), Ba‐S‐N, between the two groups. Conclusions: Cephalometry may provide information regarding persistent postoperative VPD. The nasopharyngeal space angle and velar length appear to be risk factors for persistent VPD after adenoidectomy.